Approach changing into organization processes and personnel management in context of digitalization. Issue 1 (September 2020) - Makarchenko, Marina; Borisova, Iolanta; Sattorov, Farrukh
Abstract: The virtual teams which are the subject of study becoming more significant in conditions of digitalization. The virtual team possess specific characteristics that determine a number of advantages and disadvantages and also makes changes to the processes of organization, management and control. The members of virtual teams can be divided in area and (or) in time from the position of organization, they can be beyond personal contact with each other and use different software for communication. Despite this the virtual team is endowed with a large grade of independence and the members of virtual team are share, plan and control all types of work by themselves. Most negative factor is the lack of direct communication between group members and this has a significant impact on all the problems and risks of a virtual team according to experts. It is important to implement an absolute indicator of performance evaluation in order to stimulate communication within the team. The authors propose to apply the temporarily oriented indicators as the most objective indicator of virtual team effectiveness evaluation. The advantages of this indicator are: simplicity of calculations, applicability to any teams, relevance in the context of digitalization and the common interest of all team members.